Extended space charge region and unoccupied molecular band formation in epitaxial tetrafluorotetracyanoquinodimethane films - Gerbert, David; Maaß, Friedrich; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2017)
Generating well-defined molecular structures at inorganic/organic interfaces and within molecular films is fundamental for charge carrier transport and thus the performance of organic molecule-based (opto)electronic devices. Here we show by means of low-energy electron diffraction that tetrafluorotetracyanoquinodimethane (F4TCNQ) grows in an epitaxial fashion on the Au(111) surface, resulting in a unit cell which consists of one molecule. In this well-ordered crystalline films we found the formation of an extended space charge region and a dispersing unoccupied electronic molecular state using energy- and angle-resolved two-photon photoemission. The latter finding is a clear proof for band formation in the crystalline molecular structure. We suggest that the high electron affinity of F4TCNQ and a bandlike electron transport are responsible for the formation of the space charge region. Using F4TCNQ as a hole injection layer may open the opportunity to manipulate the hole injection barrier in a controlled way via variation of the F4TCNQ layer thickness.
Gesehen am 04.05.2018